Cruise Sector Growth Managing Emerging Markets, Human Resources, Processes and Systems - Papathanassis, Alexis (Gabler Verlag : Imprint: Gabler Verlag, 2009)
Despite representing a fairly small fraction of global tourism activity, the cruise sector has been experiencing a steady growth rate over the last years. The 1st International Cruise Conference (ICC) and its proceedings documented here face the changes which accompany this process of growth. The corresponding refereed papers are organized under the following themes: New trends and innovations, human resource management, information technology and standardization. The underlying motivation behind this collection of works is to bridge the gap between cruise theory and practice, by providing a 'living research agenda' aligned with the cruise sector's realities and needs.